On the relation of negations in Nelson algebras - Gomez, Conrado Javier (2021)
The aim of this paper is to investigate the relation between the strong and the “weak” or intuitionistic negation in Nelson algebras. To do this, we define the variety of Kleene algebras with intuitionistic negation and explore the Kalman’s construction for pseudocomplemented distributive lattices. We also study the centered algebras of this variety.